Emulsifying and emulsion stabilizing properties of soy protein hydrolysates, covalently bonded to polysaccharides: The impact of enzyme choice and the degree of hydrolysis. (April 2021) - Ding, Yue; Chen, Lin; Shi, Yugang; Akhtar, Mahmood; Chen, Jianshe; Ettelaie, Rammile
Abstract: Emulsifying and emulsion stabilizing properties of fragments, derived from vegetable proteins (soy protein isolate) and covalently linked to maltodextrin have been studied. The dual role of the degree of hydrolysis (DH) in improving the solubility of soy protein isolate (SPI) on one hand and difficulties of linking hydrolysates to polysaccharide on the other, have been highlighted. The findings have been compared to results obtained for whey protein isolate (WPI) fragments, undergoing the same enzymatic fragmentation and subsequent Maillard reaction. All experiments were conducted with two very different enzymes. Trypsin is rather selective of peptide bonds it cleaves, while alcalase is less specific. At the same DH, the actions of these two enzymes on the behaviour of the resulting conjugates were found to be broadly similar for the whey protein hydrolysates. In contrast, the trypsin generated soy protein fragments showed distinctly superior emulsifying properties than those produced by alcalase. These differences were related to the physical form of SPI existing as small colloidal aggregates in solution at the time of hydrolysis, whereas WPI was present as a molecularly well-dissolved protein. It is shown that, in realizing the best emulsion stabiliser, the improved solubility as a result of a higher level of hydrolysis is offset by the deterioration of the surface functionality of polypeptides due to further fragmentation. This leads to an optimum value for the DH of vegetable proteins for synthesising the most suitable Maillard based emulsifiers. For commercial SPI used in this study this was found to be around 8%. Graphical abstract: Image 1 Highlights: Solubility of polypeptides is crucial for achieving desired Maillard conjugates. Trypsin is superior to alcalase in improving the solubility, and emulsifying properties of SPI hydrolysates. Excessive hydrolysis is detrimental to surface properties of hydrolysates or conjugates based on them. Competing needs for solubility and adequate surface properties, leads to an optimum level of hydrolysis. Optimal level of hydrolysis depends on the physical state of the protein in solution.